Choledochal Cyst in a Female Adult Asymptomatic Patient: Review of the Literature - De Simone Belinda; Del Rio Paolo; Napoli Josephine Andrea; Sianesi Mario (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2016)
Cystic disease of the bile duct is a congenital abnormality of the biliary tree that most commonly affects the neonatal population, and is uncommon after childhood, it is rarely diagnosed in adults. We report the case of a 42-year-old woman affected by choledochal cyst type I, according to Todani's classification, found unintentionally. The patient was submitted to the complete surgical excision of choledochal cyst, and discharged on the 11th postoperative day without complications.